Penarapan Teknik Sosiodrama dalam Bimbingan Kelompok untuk Meningkatkan Kemampuan Komunikasi Interpersonal Peserta Didik SMP Rajawali Makassar - Dariani, Yosepina (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
This research aims to determine 1) the level of interpersonal communication skills at Rajawali Middle School, Makassar before being given treatment. 2) Description of the implementation of sociodrama techniques in group guidance to improve interpersonal communication for class VIII at Rajawali Middle School. 3) Sociodrama techniques can improve interpersonal communication skills for class VIII at Rajawali Middle School. This research uses a quantitative approach with a one group pretest posttest design model. Data analysis uses descriptive statistical analysis and parametric analysis, namely the t test. The research results showed that: 1) The level of students' interpersonal communication skills during the pretest was in the low category. 2) Implementation of sociodrama techniques in group guidance to improve students' interpersonal communication skills at Rajawali Middle School Makassar is carried out according to designed procedures. 3) There are differences in the level of interpersonal communication skills before and after being given treatment in the form of sociodrama techniques. This means that the application of sociodramatic techniques in group guidance can improve students' interpersonal communication skill.